Analisis Kadar Kurkumin pada Herbal Oil Kunyit Ekstrak Virgin Coconut Oil dengan Metode Ultrasonik dan Maserasi: Analysis of Curcumin Levels in Turmeric Herbal Oil Extract Virgin Coconut Oil with Ultrasonic and Maceration Methods - Mahmudah, Rif'atul; Nada, Ufilia Quthrotun; Aulia, Sakinatul (KOVALEN: Jurnal Riset Kimia, 2023)
Vegetable oil theoretically and experimentally has proven its potential as an alternative solvent in the extraction of natural materials. Turmeric infused with virgin coconut oil (VCO) is a way to take advantage of the active compounds from the herbs and the oil itself. This study aims to determine the ability of the VCO solvent in extracting curcumin compounds from turmeric with the addition of tween 80 surfactants. The extraction method used was maceration at 60â„ƒ and an ultrasonic frequency of 40 kHz for 15 minutes. Thin layer chromatography (TLC) was used for qualitative analysis of each herbal oil extract using chloroform: methanol (95:5) eluent and FTIR spectrophotometer to identify functional groups. The highest curcumin content was found in herbal oil with tween 80 of 2 ml, namely 31 ppm in maceration extraction and 260.7 ppm in ultrasonic extraction. Identification of curcumin functional groups in herbal oils showed absorption patterns of O-H, C=O, aromatic C=C, C-O-C, and C-H.